Darkening song - Seddon, Delphine (Saturday Books, 2026)
"Eva is just 18 years old and interning at a record label when she discovers 16 year old Alora online. Never has she heard a voice like Alora's and when it's clear there isn't anyone at the label interested in hearing this phenomenal talent, Eva takes matters into her own hands. On a whim, Eva offers Alora representation as her manager without knowing the first thing about artist management or what's about to happen to both of them. And it turns out Eva was right... Alora is swiftly catapulted into the spotlight of major superstardom, and as the two navigate the whirling vortex of fame-the parties, the money, the paparazzi, and power-they form a deep bond, becoming found family for one another. But when Alora's dark and mysterious past begins to infiltrate her present and Eva's ambition and success blind her to the obvious signs that her client and, most importantly, her friend is in trouble, their lives unravel with disastrous consequences. DARKENING SONG is a fiercely feminist story about friendship and betrayal. It's a love story, and a story about growing up in an industry which sometimes disregards the needs of young girls and women in favour of self-interest. But more than anything, it's a story about redemption, and the ways that hopes and dreams can come true in ways we least expect"-- Provided by publisher.